Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kinerja Guru: (Studi Kasus di SDIT Ya Bunayya Pujon) - Anggriani, Nur Intan; Syarifuddin, Ahmad Arif; Prasojo, Tri Agung Yoga; Destari, Winda (Universitas Nusantara PGRI Kediri, 2023)
This study aims to describe the implementation of the principal's academic supervision in improving teacher performance at SDIT Ya Bunayya Pujon, which is a formal educational institution that plays a role in improving human resources. Teachers as teaching staff are the main component and have a very important role in carrying out teaching in schools, so their competence must be fostered and developed through supervision activities. This study used a qualitative approach, data collection was carried out by interview techniques, participatory observation, and documentation. Data analysis using the Miles and Huberman model which includes data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of the principal's academic supervision in improving teacher performance at SDIT Ya Bunayya Pujon is carried out by 1) Class Visits, 2) Class Observations, 3) Inter Visitations, 4) Personal Conversations, 5) Teacher Meetings